Hubungan Antara Motivasi dan Disiplin Kerja Dengan Produktivitas Kerja Perawat di Ruang Rawat Inap RS Melati Tangerang - Deswita, Reny; Sipah Paujiah; Popy Irawati (PT. Pubsains Nur Cendekia, 2023)
Background: Nurses' work productivity is an important factor in improving and developing the quality of hospital services. Productivity in nursing is complex and impacts patient care. If nurse productivity is low, the performance of nurses in providing nursing services will decrease. As a result, client satisfaction as recipients of nursing services is not met properly, so that the quality of nursing services decreases. Apart from that, poor nurse productivity tends to result in poor documentation quality as well. Objective: The aim of this research is to analyze the relationship between work motivation and discipline and work productivity. Method: Quantitative research with a cross sectional approach, the sample in this study was 65 respondents. This research was conducted at Melati Tangerang Hospital from April-May 2023. This research used univariate tests to identify the characteristics of respondents and bivariate tests using the Chi-Square Test were used to determine the relationship between variables. Results: there is a significant relationship between work motivation and discipline and nurses' work productivity with a p-value of 0.000. 81.5% of respondents have high work motivation, 84.6% of respondents have high work discipline and as many as 81.5% of respondents have a high level of work productivity. Conclusion: High work motivation and discipline can increase work productivity thereby improving the quality of nursing services and preventing errors in providing nursing care